Personalized earring based on natural slabstone material and manufacturing method thereof

By using epoxy resin sealing and UV glue bonding technology on natural stone slate earrings, the problems of fragility of stone and insufficient bonding strength are solved, the durability and weather resistance of earrings are improved, and the beauty of high-end products is met and practical requirements.

CN119257350AInactive Publication Date: 2025-01-07陶正璀
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411621049.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing natural stone earrings are prone to fragility during processing, insufficient structural stability and adhesive strength, and insufficient surface protection, resulting in poor durability and weather resistance, making it difficult to meet consumers' demand for high-end products.

Method used

It uses natural stone slab material with a thickness of 1mm-10mm, and the outer surface is covered with 60%-90% epoxy resin seal. UV glue is used to bond the stone to metal accessories, and cure it through ultraviolet light, combining multi-stage grinding and polishing. Ensure the structural stability and surface gloss of the earrings.

Benefits of technology

It improves the durability and weather resistance of natural stone earrings, extends service life, meets consumers' aesthetics and practicality needs for high-end products, and provides a variety of personalized design options.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119257350A_ABST
    Figure CN119257350A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ornament processing, and discloses a personalized earring based on a natural slabstone material, which comprises the following components: a natural slabstone which is selected from conglomerate, sandstone, shale, limestone and granite and has a thickness of 1-10mm, and the outer surface of the natural slabstone is covered with seal resin; the earring accessory comprises an ear hook, an ear clip or a chain and is used for connecting the natural stone plates; the UV glue is used for bonding the stone main body and the earring accessory and is cured through ultraviolet rays; the seal resin comprises the following components in percentage by mass: 60-90% of epoxy resin; 10%-40% of a curing agent; 1%-15% of a diluent; and 0.1%-5% of an antioxidant. The natural stone is adopted as the core material, and the stone has unique texture and color, so that the earring has natural aesthetic feeling and artistic value in appearance, presents diversified styles according to the characteristics of different stones, and meets the diversified aesthetic needs of consumers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of jewelry processing, in particular to a personalized ear ornament based on natural slate material and a manufacturing method thereof. Background Art

[0002] As people's demand for personalized and high-quality jewelry continues to increase, the design and material selection of earrings are also constantly innovating. The earrings on the market are mainly made of precious metals (such as gold, silver), gemstones, plastics and alloys. Although these earrings have certain aesthetics and practicality, they also have some obvious shortcomings. Although metal earrings (such as silver jewelry) are elegant in appearance, they are prone to oxidation or discoloration and require regular cleaning and maintenance; plastic earrings are light and diverse, but the texture is poor and not durable enough, and it is difficult to meet consumers' demand for high-end products. Although gemstone earrings have a sense of luxury, they are expensive and their styles are relatively fixed, making it difficult to achieve extensive personalized customization.

[0003] In recent years, natural stone has gradually gained favor among designers and consumers due to its unique texture and beauty. However, the research and application of using natural stone as earring materials in the existing technology is still relatively limited, mainly facing the following technical difficulties:

[0004] The brittleness of stone: Natural stone is easy to break during processing, and special processing technology is required to improve its structural stability. Ordinary processing methods cannot guarantee its yield and surface integrity, which puts higher requirements on the durability of the jewelry.

[0005] Insufficient structural stability and bonding strength: Traditional adhesives are difficult to form a strong bond between stone and metal accessories, causing the earring structure to loosen or fall off easily during long-term use. Especially in humid or temperature-swinging environments, the bonding performance is often unstable, affecting the service life of the earrings.

[0006] Insufficient surface protection: Stone earrings may wear out or fade due to friction, oxidation and other factors during long-term wear. The existing technology lacks effective surface sealing technology to improve its weather resistance and glossiness. Ordinary sealing materials may affect the appearance and performance of the jewelry due to uneven coverage or insufficient hardening.

[0007] To this end, those skilled in the art provide a personalized earring based on natural slate material and a method for making the same to solve the problems raised in the above background technology. Summary of the invention

[0008] In view of the deficiencies in the prior art, the present invention provides a personalized ear ornament based on natural slate material and a method for making the same, which solves the problem that there is a lack of research and application of using natural stone as ear ornament material.

[0009] To achieve the above objectives, the present invention is implemented through the following technical solutions: a personalized earring based on natural slate material, comprising the following components:

[0010] Natural stone slabs, selected from conglomerate, sandstone, shale, limestone and granite, with a thickness of 1mm-10mm, the outer surface of which is covered with a sealing resin;

[0011] Ear accessories, including ear hooks, clips or chains, for attaching natural stone slabs;

[0012] UV glue is used to bond the stone body to the earring accessories and is cured by ultraviolet rays.

[0013] Preferably, the sealing resin comprises the following components in percentage by mass:

[0014] 60%-90% epoxy resin;

[0015] 10%-40% curing agent;

[0016] 1%-15% diluent;

[0017] 0.1%-5% antioxidants.

[0018] Preferably, the earring accessories are made of materials including but not limited to 316L stainless steel, 925 silver or gold-plated alloy.

[0019] Preferably, the UV glue is an acrylic adhesive.

[0020] A method for making personalized earrings based on natural slate material, according to a method for making personalized earrings based on natural slate material, comprising the following steps:

[0021] S1. Select natural slate or stone and clean it with cleaning fluid;

[0022] S2. Use cutting equipment to cut the stone into the required shape, and the cutting error is controlled within the range of ±0.1mm-0.5mm;

[0023] S3. Perform preliminary and fine grinding on the stone. Use 60-500 mesh sandpaper for preliminary grinding and 600-3000 mesh sandpaper for fine grinding.

[0024] S4, drilling holes in the stone using a drilling machine;

[0025] S5. Spray sealing resin on the surface of the stone;

[0026] S6. Polish the stone with polishing paste;

[0027] S7, bonding the earring accessories to the stone body and curing them with an ultraviolet lamp;

[0028] S8. Conduct tensile test and weather resistance test.

[0029] Preferably, the cleaning solution in step S1 comprises the following components in percentage by mass:

[0030] 40%-60% ethanol;

[0031] 30%-50% distilled water;

[0032] 1%-10% nonionic surfactant.

[0033] Preferably, the polishing paste formula in step S6 includes the following components in mass percentage:

[0034] 50%-80% alumina;

[0035] 10%-50% cerium oxide;

[0036] 1%-15% abrasive.

[0037] Preferably, the temperature of the sealing layer curing process in step S5 is 30° C.-70° C., and the time is 12 hours-48 hours.

[0038] Preferably, in the step S4, the aperture range is 0.5 mm-2 mm, and the aperture tolerance is controlled within the range of ±0.1 mm-0.3 mm.

[0039] Preferably, the weather resistance test environment in step S8 is placed in an environment with a humidity of 50%-80% and a temperature of 20°C-50°C for 24 hours to 72 hours.

[0040] The present invention provides a personalized ear ornament based on natural slate material and a method for making the same. It has the following beneficial effects:

[0041] The present invention adopts natural stones such as conglomerate, sandstone, shale, limestone and granite as core materials. These stones themselves have unique textures and colors, so that the earrings have both natural beauty and artistic value in appearance. According to the characteristics of different stones, the earrings can present a variety of styles to meet the diverse aesthetic needs of consumers. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 It is a schematic diagram of the production process of the present invention. DETAILED DESCRIPTION

[0043] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Embodiment 1:

[0045] Please see attached Figure 1 The embodiment of the present invention provides a personalized earring based on natural slate material, comprising the following components:

[0046] The natural stone slab is selected from conglomerate, sandstone, shale, limestone and granite, with a thickness of 1 mm to 10 mm, and its outer surface is covered with a sealing resin; the sealing resin includes the following components in mass percentage:

[0047] 60%-90% epoxy resin;

[0048] 10%-40% curing agent;

[0049] 1%-15% diluent;

[0050] 0.1%-5% antioxidants.

[0051] Specifically, natural stone slabs are used as the core material of earrings. Natural stone slabs are selected from conglomerate, sandstone, shale, limestone and granite, and the thickness is controlled between 1mm and 10mm. These stones each have unique physical properties and aesthetic value, so that the earrings not only have natural textures and colors, but also show the unique texture and artistry of the stone to a certain extent. Marble is known for its smooth surface and rich color texture, which is suitable for earring designs that require a high-end and luxurious feel; the layered structure of shale gives earrings a natural and simple beauty, which is especially suitable for consumers who advocate a natural style; basalt is excellent in its high hardness and wear resistance, and is suitable for durable earring designs for daily wear. Through the reasonable selection and processing of these stones, earrings can meet the needs of beauty while being practical and durable.

[0052] In order to further improve the surface weather resistance, water resistance and corrosion resistance of the earrings, the present invention uses a sealing resin to cover the outer surface of the stone. The sealing layer can not only effectively improve the smoothness and glossiness of the stone surface, but also prevent fading, cracking and structural deformation caused by environmental changes. The formula of the sealing resin is scientific and reasonable, and specifically includes the following components in mass percentage: 60%-90% epoxy resin, 10%-40% curing agent, 1%-15% diluent and 0.1%-5% antioxidant.

[0053] As the main component of the sealing resin, epoxy resin has excellent adhesion and mechanical properties. After curing, it can form a high-strength protective film, giving the surface of the earrings excellent wear resistance and impact resistance. At the same time, the transparency of epoxy resin can retain and enhance the original texture and color of natural stone, making the appearance of the earrings more beautiful. The addition of curing agent allows the epoxy resin to harden quickly and form a uniform cross-linked structure during the curing process, which improves the structural stability of the earrings and avoids deformation and loosening caused by temperature or humidity changes. The use of diluent can adjust the viscosity of the resin, ensure the convenience of operation during the sealing process, and enable the resin to be evenly applied to the surface of the stone, thereby ensuring that the thickness of the sealing layer is consistent and free of bubbles. As an important component in the resin formula, antioxidants can effectively prevent oxidation of earrings due to long-term exposure to air, extend the service life of the sealing layer, and ensure that the appearance of the earrings is long-lasting and beautiful.

[0054] After the earrings are sealed, they can maintain their structural integrity and surface gloss when the environmental conditions such as humidity and temperature change. In addition, the seal can effectively prevent the stone from being damaged by daily wear and tear or chemical corrosion, greatly extending the service life of the earrings.

[0055] Ear accessories, including ear hooks, ear clips or chains, used to connect natural stone slabs; materials of ear accessories include but are not limited to 316L stainless steel, 925 silver or gold-plated alloy.

[0056] Specifically, the ear accessories are an important component of the natural slate ear accessories of the present invention, and are mainly used to firmly connect the stone body to the wearing structure. The ear accessories include ear hooks, ear clips or chains, which can be flexibly selected according to different wearing needs and design styles. Ear hooks are suitable for pierced ear accessories, which are easy to wear and suitable for lightweight designs; ear clips provide convenience for users who do not have pierced ears, ensuring the universality of ear accessories; chains are used to connect ear accessories with multiple structures, making them more layered and designed. In order to ensure the durability and wearing comfort of the ear accessories, the material of the ear accessories is required to be high-strength, corrosion-resistant and non-allergenic, specifically including but not limited to 316L stainless steel, 925 silver or gold-plated alloy.

[0057] 316L stainless steel has excellent anti-rust and anti-corrosion properties, is suitable for daily wear and is not easy to change color; its low allergenicity also makes it an ideal choice for people with sensitive skin. 925 silver is often used in high-end jewelry due to its classic luster and elegant appearance, but it needs to be treated with anti-oxidation to extend its service life. Gold-plated alloys have both metallic texture and color diversity, providing more creative options for design, and maintaining a low cost while improving the overall aesthetics of the earrings. In addition, these metal materials not only have good mechanical properties and can withstand the pulling and collision during daily wear, but also have sufficient processing performance and can be firmly bonded to natural stone slabs. The flexible selection and reasonable design of accessories make the earrings of the present invention both beautiful and functional, providing a diverse wearing experience for different user groups.

[0058] UV glue is used to bond the stone body to the earring accessories and is cured by ultraviolet light. UV glue is an acrylic adhesive.

[0059] Specifically, UV glue is the key adhesive material in the natural stone earrings of the present invention, which is used to firmly bond the stone body to the earring accessories and form a high-strength connection through ultraviolet curing. UV glue uses an acrylic adhesive, whose chemical structure allows it to cure in a short time and has excellent bonding properties. Acrylic glue rapidly undergoes polymerization reaction under ultraviolet irradiation to form a dense cross-linked structure, which not only improves the bonding strength, but also ensures the connection stability during long-term use. The rapid curing characteristics of the glue significantly improve the process efficiency and reduce the problems of long curing time and unstable bonding strength of traditional glues.

[0060] In addition, acrylic ester UV glue has excellent weather resistance, can withstand changes in temperature and humidity, is not prone to aging and cracking, and ensures the durability and stability of the earrings during long-term wear. At the same time, this type of glue has good transparency after curing, avoiding affecting the beauty of the stone and accessories, so that the earrings as a whole maintain a clean and natural visual effect. Since the glue itself does not contain harmful solvents, it has little impact on the human body and the environment during use, meets environmental protection requirements, and is suitable for direct use in accessories that come into contact with the skin. In addition, UV glue has a wide range of bonding adaptability and can effectively bond a variety of materials, such as metals, alloys and natural stones, ensuring the diversified design and functionality of the earrings of the present invention. Earrings bonded with UV glue are not only structurally stable, but also excel in aesthetics and durability, providing consumers with more efficient, environmentally friendly and reliable products.

[0061] A method for making personalized earrings based on natural slate material, comprising the following steps:

[0062] S1. Select natural slate or stone and clean it with a cleaning solution. The cleaning solution in step S1 includes the following components in percentage by weight:

[0063] 40%-60% ethanol;

[0064] 30%-50% distilled water;

[0065] 1%-10% nonionic surfactant.

[0066] S2. Use cutting equipment to cut the stone into the required shape, and the cutting error is controlled within the range of ±0.1mm-0.5mm;

[0067] S3. Perform preliminary and fine grinding on the stone. Use 60-500 mesh sandpaper for preliminary grinding and 600-3000 mesh sandpaper for fine grinding.

[0068] S4. Use a drilling machine to drill holes in the stone; the hole diameter range is 0.5mm-2mm, and the hole diameter tolerance is controlled within the range of ±0.1mm-0.3mm

[0069] S5. Spray the sealing resin on the surface of the stone; the temperature of the sealing resin curing process is 30℃-70℃, and the time is 12H-48H

[0070] S6. Polish the stone using a polishing paste; the polishing paste formula includes the following components in percentage by mass:

[0071] 50%-80% alumina;

[0072] 10%-50% cerium oxide;

[0073] 1%-15% abrasive;

[0074] S7, bonding the earring accessories to the stone body and curing them with an ultraviolet lamp;

[0075] S8. Conduct tensile test and weather resistance test. The weather resistance test environment is placed in an environment with a humidity of 50%-80% and a temperature of 20℃-50℃ for 24H-72H.

[0076] Specifically, first, in step S1, natural stones such as conglomerate, sandstone, shale, limestone and granite are selected and thoroughly cleaned with a cleaning solution consisting of 40%-60% ethanol, 30%-50% distilled water and 1%-10% non-ionic surfactant to ensure that the surface of the stone is free of grease and impurities, providing a good foundation for subsequent processing. In step S2, the stone is accurately cut into the required shape using cutting equipment, and the cutting error is strictly controlled between ±0.1mm-0.5mm to ensure that the stone size is consistent with the design drawing and to avoid damage to the stone structure during the cutting process. In step S3, the stone surface is processed by preliminary and fine grinding. The preliminary grinding uses 60-500 mesh sandpaper to remove rough edges, and the fine grinding uses 600-3000 mesh sandpaper to make the stone surface smooth and flat. Next, in step S4, a drilling machine is used to perform drilling processing, with a hole diameter range of 0.5mm-2mm and a tolerance controlled within ±0.1mm-0.3mm to ensure that the hole diameter accurately matches the specifications of the earring accessories.

[0077] After the stone processing is completed, enter step S5, spray the sealing resin evenly on the surface of the stone, and cure it in a temperature environment of 30℃-70℃ for 12 hours-48 hours to ensure that the resin is closely combined with the surface of the stone to improve the weather resistance and protective performance of the earrings. Subsequently, in step S6, the stone is polished with a polishing paste composed of 50%-80% aluminum oxide, 10%-50% cerium oxide and 1%-15% abrasive to give it a natural luster and exquisite texture. Then, in step S7, the earring accessories are bonded to the main body of the stone, and UV glue is used as an adhesive, which is quickly cured under ultraviolet light to ensure the stability and durability of the structure. In the final step S8, the finished earrings are subjected to tensile tests and weather resistance tests. The weather resistance test needs to be placed in an environment with a humidity of 50%-80% and a temperature of 20℃-50℃ for 24 hours-72 hours to verify the stability and performance of the earrings under different environmental conditions. This production method ensures the comprehensive performance of the earrings in terms of aesthetics, durability and structural stability, and meets the market demand for high-quality personalized earrings through scientific process flow.

[0078] Embodiment 2:

[0079] The embodiment of the present invention provides a personalized earring made of natural shale material based on embodiment 1;

[0080] Shale is selected as the natural stone, and its unique layered texture is used to increase the natural beauty of the earrings.

[0081] Material selection: Shale thickness is 2mm.

[0082] Cleaning step (S1): using a cleaning solution containing 50% ethanol, 45% distilled water, and 5% non-ionic surfactant for cleaning, and using ultrasonic equipment to remove impurities on the shale surface.

[0083] Cutting step (S2): using laser cutting equipment to cut the shale stone into a circle with an error controlled within ±0.2 mm.

[0084] Polishing step (S3):

[0085] Use 80-grit sandpaper for initial grinding to remove rough edges on the stone surface;

[0086] Fine sanding using 1000 grit sandpaper to smooth the surface.

[0087] Drilling step (S4): the drilling hole diameter is 1.0 mm, and the tolerance is controlled within ±0.2 mm.

[0088] Sealing treatment (S5):

[0089] The sealing resin formula is 70% epoxy resin, 25% curing agent, 4% diluent, and 1% antioxidant;

[0090] The curing temperature is 50°C and the curing time is 24 hours.

[0091] Polishing step (S6): polishing is performed using a polishing paste, the formula of the polishing paste being: 70% aluminum oxide, 20% cerium oxide, and 10% abrasive.

[0092] Bonding step (S7): The ear hook is bonded to the shale body using acrylic UV glue and cured under an ultraviolet lamp for 30 seconds.

[0093] Test step (S8): The finished product is placed under the conditions of 70% humidity and 30°C for 48 hours to ensure structural stability.

[0094] Summary: Shale is used as the material to show the natural layered texture. The texture of the stone is retained after fine polishing, which is suitable for natural style design. The curing time is moderate to ensure that the earrings are highly weather-resistant. Suitable for users who like natural style and simple design.

[0095] Embodiment 3:

[0096] The embodiment of the present invention provides a minimalist earring made of natural conglomerate material based on embodiment 1;

[0097] Conglomerate was chosen for its wear resistance and designed as a minimalist earring.

[0098] Material selection: Conglomerate thickness is 5mm.

[0099] Cleaning step (S1): using a cleaning solution containing 40% ethanol, 50% distilled water, and 10% non-ionic surfactant to clean the surface of the gravel.

[0100] Cutting step (S2): cutting into a rectangular shape with an error controlled within ±0.1 mm.

[0101] Polishing step (S3):

[0102] Use 120-grit sandpaper for initial sanding;

[0103] For fine sanding use 2000 grit sandpaper.

[0104] Drilling step (S4): the drilling hole diameter is 0.8 mm, and the tolerance is controlled within ±0.1 mm.

[0105] Sealing treatment (S5):

[0106] The sealing resin formula is 85% epoxy resin, 10% curing agent, 4% diluent, and 1% antioxidant;

[0107] The curing temperature is 60°C and the curing time is 12 hours.

[0108] Polishing step (S6): using a polishing paste of 80% aluminum oxide and 20% cerium oxide to give the conglomerate surface a natural luster.

[0109] Bonding step (S7): Use UV glue to bond the earring accessories and cure them under ultraviolet light for 20 seconds.

[0110] Test step (S8): Place in an environment with a humidity of 60% and a temperature of 25° C. for 24 hours to test the structural stability and weather resistance.

[0111] Summary: The conglomerate material is wear-resistant and impact-resistant, suitable for daily wear. The earrings are simple in design and the craftsmanship is minimalist. The high-temperature rapid curing seal improves durability and protection. Suitable for users who want earrings that are durable and not easily deformed.

[0112] Embodiment 4:

[0113] The embodiment of the present invention provides a luxury earring made of natural granite based on embodiment 1;

[0114] Choose granite to showcase its natural texture and high gloss characteristics, suitable for high-end design styles.

[0115] Material selection: Granite thickness is 3mm.

[0116] Cleaning step (S1): Cleaning is performed using a cleaning solution containing 60% ethanol, 35% distilled water, and 5% non-ionic surfactant.

[0117] Cutting step (S2): cutting the granite into an elliptical shape, with the cutting error controlled within ±0.3 mm.

[0118] Polishing step (S3):

[0119] Use 100-grit sandpaper for initial sanding;

[0120] Use 3000 grit sandpaper for fine grinding to achieve a mirror finish.

[0121] Drilling step (S4): the drilling hole diameter is 1.5 mm, and the tolerance is controlled within the range of ±0.2 mm.

[0122] Sealing treatment (S5):

[0123] The sealing resin formula is 65% epoxy resin, 30% curing agent, 4% diluent, and 1% antioxidant;

[0124] The curing temperature is 30°C and the curing time is 48 hours.

[0125] Polishing step (S6): using a polishing paste having a formula of 50% aluminum oxide, 40% cerium oxide, and 10% abrasive.

[0126] Bonding step (S7): The granite body is bonded to the gold-plated ear clip and cured by ultraviolet light for 60 seconds.

[0127] Test step (S8): After being placed in an environment with a humidity of 80% and a temperature of 20° C. for 72 hours, the weather resistance is tested.

[0128] Summary: Granite material has its own texture and high gloss, suitable for high-end design. Mirror polishing treatment shows the luxury of earrings. The curing temperature is low and the curing time is long to ensure that the seal layer is well integrated with the stone. It is suitable for high-end occasions and meets the needs of users who pursue exquisiteness and fashion.

[0129] Embodiment 5:

[0130] The embodiment of the present invention provides a multi-material mixed earring design based on embodiment 1;

[0131] Combine different types of natural stones together to create multi-material mixed earrings.

[0132] Material selection: shale thickness is 2mm, granite thickness is 4mm.

[0133] Cleaning step (S1): Cleaning is performed using a cleaning solution of 50% ethanol, 45% distilled water, and 5% non-ionic surfactant.

[0134] Cutting step (S2): cutting shale into squares and granite into circles, and controlling the cutting error within the range of ±0.5 mm.

[0135] Polishing step (S3):

[0136] Initial grinding: Use 80-grit sandpaper to sand the shale;

[0137] Fine Sanding: Use 2000 grit sandpaper to sand the granite.

[0138] Drilling step (S4): holes are drilled in shale and granite respectively, with the hole diameters of both being 1.0 mm and the tolerance being controlled within the range of ±0.2 mm.

[0139] Sealing treatment (S5):

[0140] The sealing resin was sprayed on the shale and granite respectively, with the curing temperature at 40°C and the curing time for 24 hours.

[0141] Polishing step (S6): using a polishing paste formulated with aluminum oxide and cerium oxide for treatment.

[0142] Bonding step (S7): Use UV glue to combine the shale and granite body, fix the ear hook, and cure it by ultraviolet light.

[0143] Test step (S8): Test for 48 hours at a humidity of 75% and a temperature of 30°C to ensure that the structure is stable.

[0144] Summary: The combination of shale and granite forms a unique mixed design. The mix of different stones provides rich texture and layering, which is suitable for personalized customization, meets the diverse needs of consumers, emphasizes creativity and uniqueness, and is suitable for young users and customized markets.

[0145] Summary:

[0146] The various embodiments of the present invention demonstrate the flexible application of different stone materials and design styles, and embody the following advantages:

[0147] Diverse material selection: By using natural stones such as granite, shale and conglomerate, earrings have a variety of options in appearance and texture, meeting different market demands from natural style to luxury style.

[0148] High durability and environmental protection: The use of sealing resin and UV glue bonding technology makes the earrings have good weather resistance and protection, and reduces chemical pollution, meeting environmental protection requirements.

[0149] Flexible process and customized design: The process flow in each embodiment (such as multi-stage grinding, drilling, polishing and sealing) can be adjusted according to different needs to support large-scale production and personalized customization.

[0150] Applicable to a wide range of scenarios: Earrings can meet the needs of daily wear, luxurious occasions and personalization, and are suitable for different age groups and consumer groups.

[0151] In summary, the present invention provides the market with personalized earrings with high quality and artistic value through efficient production technology and flexible application of diversified materials, meeting the needs of modern consumers for beautiful, environmentally friendly and durable products.

[0152] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A personalized earring based on natural slate material, characterized in that: Includes the following components: Natural stone slabs, selected from conglomerate, sandstone, shale, limestone and granite, with a thickness of 1mm-10mm, the outer surface of which is covered with a sealing resin; Ear accessories, including ear hooks, clips or chains, for attaching natural stone slabs; UV glue is used to bond the stone body to the earring accessories and is cured by ultraviolet rays.

2. The personalized earrings based on natural stone material according to claim 1, characterized in that: The sealing resin comprises the following components in percentage by weight: 60%-90% epoxy resin; 10%-40% curing agent; 1%-15% diluent; 0.1%-5% antioxidants.

3. The personalized earrings based on natural stone material according to claim 1, characterized in that: The earring accessories materials include but are not limited to 316L stainless steel, 925 silver or gold-plated alloy.

4. The personalized earrings based on natural stone material according to claim 1, characterized in that: The UV glue is an acrylic adhesive.

5. A method for making personalized earrings based on natural stone slab materials, according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Select natural slate or stone and clean it with cleaning fluid; S2. Use cutting equipment to cut the stone into the required shape, and the cutting error is controlled within the range of ±0.1mm-0.5mm; S3. Perform preliminary and fine grinding on the stone. Use 60-500 mesh sandpaper for preliminary grinding and 600-3000 mesh sandpaper for fine grinding. S4, drilling holes in the stone using a drilling machine; S5. Spray sealing resin on the surface of the stone; S6. Polish the stone with polishing paste; S7, bonding the earring accessories to the stone body and curing them with an ultraviolet lamp; S8. Conduct tensile test and weather resistance test.

6. The method for making personalized earrings based on natural stone material according to claim 5, characterized in that: The cleaning solution in step S1 includes the following components in percentage by weight: 40%-60% ethanol; 30%-50% distilled water; 1%-10% nonionic surfactant.

7. The method for making personalized earrings based on natural stone slab material according to claim 5, characterized in that: The polishing paste formula in step S6 includes the following components in percentage by mass: 50%-80% alumina; 10%-50% cerium oxide; 1%-15% abrasive.

8. The method for making personalized earrings based on natural stone slab material according to claim 5, characterized in that: The temperature of the sealing layer curing process in step S5 is 30° C.-70° C. and the time is 12 hours-48 hours.

9. The method for making personalized earrings based on natural stone material according to claim 5, characterized in that: In the step S4, the aperture range is 0.5 mm-2 mm, and the aperture tolerance is controlled within the range of ±0.1 mm-0.3 mm.

10. The method for making personalized earrings based on natural stone material according to claim 5, characterized in that: The weather resistance test environment in step S8 is placed in an environment with a humidity of 50%-80% and a temperature of 20°C-50°C for 24 hours-72 hours.